Comparative functional expression of nAChR subtypes in rodent DRG neurons - Smith, Nathan J.; Hone, Arik J.; Memon, Tosifa; Bossi, Simon; Smith, Thomas E.; McIntosh, J. M.; Olivera, Baldomero M.; Teichert, Russell W. (Frontiers in Cellular Neuroscience, 2013)
We investigated the functional expression of nicotinic acetylcholine receptors (nAChRs) in heterogeneous populations of dissociated rat and mouse lumbar dorsal root ganglion (DRG) neurons by calcium imaging. By this experimental approach, it is possible to investigate the functional expression of multiple receptor and ion-channel subtypes across more than 100 neuronal and glial cells simultaneously. Based on nAChR expression, DRG neurons could be divided into four subclasses: 1) neurons that express predominantly alpha3beta4 and alpha6beta4 nAChRs; 2) neurons that express predominantly alpha7 nAChRs; 3) neurons that express a combination of alpha3beta4/alpha6beta4 and alpha7 nAChRs; and 4) neurons that do not express nAChRs. In this comparative study, the same four neuronal subclasses were observed in mouse and rat DRG. However, the expression frequency differed between species: substantially more rat DRG neurons were in the first three subclasses than mouse DRG neurons, at all developmental time points tested in our study. Approximately 70-80% of rat DRG neurons expressed functional nAChRs, in contrast to only ~15-30% of mouse DRG neurons. Our study also demonstrated functional coupling between nAChRs, voltage-gated calcium channels and mitochondrial Ca2+ transport in discrete subsets of DRG neurons. In contrast to the expression of nAChRs in DRG neurons, we demonstrated that a subset of non-neuronal DRG cells expressed muscarinic acetylcholine receptors (mAChRs) and not nAChRs. The general approach to comparative cellular neurobiology outlined in this paper has the potential to better integrate molecular and systems neuroscience by uncovering the spectrum of neuronal subclasses present in a given cell population and the functionally integrated signaling components expressed in each subclass.